AUDIO-VISUAL BASED PAI LEARNING STRATEGIES TO IMPROVE STUDENT OUTCOMES AT SDN 003 SUNGAI ULU - Ayumi Safitri Ayumi; Waslun; Ferri Irawan (SOSIOEDUKASI, 2026)
This study aims to examine the implementation of audio-visual based Islamic Religious Education (PAI) learning strategy and its effectiveness in improving student learning outcomes at a public elementary school in Sungai Ulu. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, classroom observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the strategy was implemented through a structured pedagogical cycle consisting of pre-lesson media preparation, facilitated active viewing via projector, and post-viewing reflective discussion, applied consistently across PAI topics including Quranic letter recognition and inspirational Islamic narratives. The strategy produced significant improvements in student learning outcomes at cognitive, affective, and participatory levels. Three factors were identified as primary drivers of effectiveness: curriculum-aligned content selection, the teacher's active facilitation competency, and consistency of implementation. Critically, this study demonstrates that teacher pedagogical agency, rather than institutional infrastructure, is the most decisive determinant of audio-visual learning success in resource-constrained rural settings. These findings contribute field-validated evidence supporting SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities), affirming that inclusive and effective PAI instruction is achievable across underserved educational contexts in Indonesia.